Bio-refinery of plant drinks press cake permeate using ultrafiltration and lactobacillus fermentation into antimicrobials and its effect on the growth of wheatgrass in vivo. (April 2022) - Trakselyte-Rupsiene, Karolina; Juodeikiene, Grazina; Alzbergaite, Gabriele; Zadeike, Daiva; Bartkiene, Elena; Ozogul, Fatih; Rueller, Lukas; Robert, Josef; Rocha, João Miguel F.
Abstract: For sustainable plant drinks production, the biorefinery concept of obtained press cakes (PC) using ultrasonication, mechanical separation, and ultra-filtration was designed in Fraunhofer UMSICHT (Germany). In this study obtained permeates, as wastes after ultrafiltration of PC (soyabeans, almonds, coconut, oats, and rice) were analyzed and their bio-stimulatory effect on the growth of wheatgrass in vivo was investigated. Permeates with higher soluble protein content (soy, almonds, and coconut) resulted in a significant increase in germination parameters (germination percentage (GP), length of stem and root as well as biomass of stem and root increased on averge by 8.3%, 15.8%, 9.2%, 2.22 times and 1.8 times, respectively) compared to the control treatment. Additionally, the fermentation using antimicrobial lactic acid bacteria (LAB) strains ( Lactobacillus brevis LUHS173, Pediococcus acidilactici LUHS236 and Lactobacillus farraginis LUHS206) was applied for bio-treatment of permeates. The efficiency of fermentation process was evaluated on the changes of pH, TTA, LAB growth kinetics and lactic acid and its isomers production. Furthermore, the antifungal activity of selected fermented products against fungi ( Fusarium graminearum F, F. graminearum, and F. culmorum ) was determined. It was found that the highest antifungal activity (18.0 mm and 16.5 mm, respectively) was obtained by 48 h fermentation of permeates from grain press cake (oats and rice), containing the most reducing saccharides, and they significantly improved the germination of contaminated grains. Innovations in the sustainable production of plant-origin drinks enable to implementation of new, environmentally friendly technologies in food sector. Highlights: Biorefinery approach can be applied for the treatment of plant drinks press cakes. Permeates from plant drink production are suitable media for fermentation with LAB. Protein-based permeates significantly improved the growth of wheatgrass. Permeates rich in reducing sugars resulted in high antifungal activity. Germination of contaminated seeds can be improved fermented permeates.